2022
DOI: 10.3390/healthcare10122473
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care for Nurses and Midwives: Findings from a Scoping Review

Abstract: Self-care for health care professionals is essential in order to optimize the care they provide and to prevent serious consequences for their health. This scoping review aimed to identify (a) the concepts used in the literature to describe self-care; (b) interventions that influence self-care. The scoping review was conducted according to the criteria and methodology by Arksey and O’Malley, from November 2020 to January 2021, by consulting the following databases: Pubmed, CINAHL, Scopus, PsycInfo, Cochrane Lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Further, the self-care agency is also related to the individuals' ability to perform the self-care activities and physical condition, and demonstrate a level of independence, based on the availability of assistance (Narasimhan et al, 2019;Sist et al, 2022). The self-care agency, in the context of breast cancer survivors, is related to estimative self-care activities, including the process of seeking knowledge about necessary self-care activities and a description of their ability to do it.…”
Section: Antecedents and Consequencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the self-care agency is also related to the individuals' ability to perform the self-care activities and physical condition, and demonstrate a level of independence, based on the availability of assistance (Narasimhan et al, 2019;Sist et al, 2022). The self-care agency, in the context of breast cancer survivors, is related to estimative self-care activities, including the process of seeking knowledge about necessary self-care activities and a description of their ability to do it.…”
Section: Antecedents and Consequencesmentioning
confidence: 99%
“…( Sist et al, 2022) Nursing Individual actions to improve and maintain their health through symptom monitoring (self-care maintenance), with information support from the health professionals in improving psychomotor self-care abilities (self-care support), or their ability to manage symptoms (self-management), and side effects of certain treatments.…”
Section: Antecedents and Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of self-care is not new, but it has recently received a new focus in global health policy. It originated with theorist Dorothea E. Orem in 1956 and has evolved over the years to the present day [1]. The World Health Organization defines self-care as "the ability of individuals, families, and communities to promote health, prevent disease, maintain health, and cope with illness and disability, with or without the support of a health professional" [2].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that MBIs can help reduce anxiety and perceived stress, preventing mental disorders (such as depression) and increasing well-being, resilience, and compassion (Fulambarkar et al, 2022;Hofmann & Gómez, 2017;Malik & Annabi, 2022;Sist et al, 2022;Zhang et al, 2020). Mindfulness is an effective method recognized and applied globally as an evidence-based psychopractice.…”
mentioning
confidence: 99%